Analisa Injector Gas Pada Flooding Di Dalam Aliran Gas Berdiameter Kecil - Erizal Erizal (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
Have been [done/conducted] [by] research about gas injector position influence [at] contrary liquid gas stream transition [of] direction in vertical channel ( flooding). Channel diameter 25,4 mm with [job/activity] fluid consist of air and water. Dilution injector in the form of wall have pore [to] residing in channel tabletop and gas injektdr in form of berdiameger channel 10 mm. First position, gas ijektor attached in the middle of channel underside ( hypodermic by aksial) and second position attached [by] [in] undercarriage channel wall ( hypodermic by radial). Result of research indicate that gas injector position [do] not so have an effect on to flooding mechanism but very having an effect on to its critical velocity. [At] is second [of] this position [of] flooding [is] always started from under with the existence of stricture [of] channel by dilution film, while location [of] gas injector [in] wall will quicken flooding march of events. Result of measurement [of] speed [of] criticism compared to result from Wallis and Dukler. [is] same Result only go into effect [at] area speed [of] dilution / certain gas.